2010
DOI: 10.1007/s11106-010-9206-8
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-like metastable phases in the Fe–Mo system: experimental study and thermodynamic modeling. I. Crystalline state of Fe–Mo melt-spinning alloys

Abstract: The β-Mn structure (π-phase) is revealed on contact and free surfaces of Fe 63 Mo 37 melt-spinning ribbons. The full-profile analysis (Rietveld analysis) of diffraction patterns for a mixture of polycrystalline phases has identified, along with the metastable π phase, bcc solid solutions, µ and σ phases, and an intermediate bcc phase in the Fe-Mo phase diagram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…In the first part of this study [3], the metastable π-phase with β-Mn structure was identified in meltspinning 63Fe37Mo alloys. Besides this phase, μ-and σ-phases, bcc solid solutions rich in iron (α 1 ) and molybdenum (α 3 ), and metastable intermediate bcc phase (α 2 ) were revealed on both the contact and free surfaces of the melt-spinning ribbons.…”
Section: Abstract Thermodynamic Modeling Fe-mo System Metastable Phmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first part of this study [3], the metastable π-phase with β-Mn structure was identified in meltspinning 63Fe37Mo alloys. Besides this phase, μ-and σ-phases, bcc solid solutions rich in iron (α 1 ) and molybdenum (α 3 ), and metastable intermediate bcc phase (α 2 ) were revealed on both the contact and free surfaces of the melt-spinning ribbons.…”
Section: Abstract Thermodynamic Modeling Fe-mo System Metastable Phmentioning
confidence: 99%
“…Under this combination of thermodynamic and kinetic approaches, one of the ways is to calculate metastable phase diagrams, one or several phases being excluded from consideration. It is assumed that the formation of phases under these conditions (for example, in rapid quenching) is impossible or difficult due to kinetic features of the process.In the first part of this study [3], the metastable π-phase with β-Mn structure was identified in meltspinning 63Fe37Mo alloys. Besides this phase, μ-and σ-phases, bcc solid solutions rich in iron (α 1 ) and molybdenum (α 3 ), and metastable intermediate bcc phase (α 2 ) were revealed on both the contact and free surfaces of the melt-spinning ribbons.…”
mentioning
confidence: 99%
“…Computational thermodynamic approaches using the CALPHAD approach (calculation of phase diagrams) are widely used, and allow you to calculate equilibrium and metastable phase transformations based on a set of mutually agreed thermodynamic parameters of system phases [14]. The thermodynamic properties of each phase that takes part in the transformations are described by appropriate models, which for phases of constant composition should take into account the temperature dependence, and, in addition, for phases that have a region of homogeneity, the temperature-concentration dependence of the Gibbs energy [15]. This approach was used to model the behavior of the multicomponent reacting systems Nb-Ni-Si [16], Cr-Mn-Si [17], C-Nb-Mo [18], B-Fe-Ti [19], B-Mo-Ti [20], B-Mo-Nb [21], V-Ti-B [22], and many others, and allowed modeling of the corresponding state diagrams.…”
Section: Introductionmentioning
confidence: 99%